Utopia e catastrofe. Pensieri al bivio tra le configurazioni originali del XIX secolo - Montanelli, Marina (Aesthetica Preprint, 2023)
The article returns to the upheaval introduced into the relationship between human beings, nature and technique by modernity through Walter Benjamin’s Arcades Project. The starting point is the formulation of the dialectical image of the 1935 exposé as a dream image. From here, the links between the collective imaginary and the transformations that affected 19th century society are analysed. The oscillation between “golden age” and “hell” turns out to be the fundamental phantasmagoria as a result of the lack of critical elaboration of technical development. Hence, some of the questions posed by the Arts and Crafts Movement, the dispute between the École Polytechnique and the École des Beaux-Arts, the reactive or compensatory responses of the art pour l’art, neoclassicism and Jugendstil to technical reproducibility and the engineering principle, the emergence of Kitsch as an aesthetic, anthropological and political category are re-examined. This clarifies Benjamin’s methodological proposal: immersion, yes, in the dreams of an epoch, but in order to grasp their internal dialectical and emancipatory force, beyond the oscillation between utopia and catastrophe.